Gallbladder Wall thickness (GBWT); A diagnostic tool of severe dengue infection: A Case Report and Literature Review - Muhamad Rafiqi Hehsan; Lau Soo Sin; Huda Zainal Abidin; Rosidah Ibrahim; Melor Mohd Mansor (Elsevier, 2024)
Non-Indexed Publication